Tidal Reconstruction of Neutron Star Mergers from Their Late Inspiral - Souradeep Pal; Rajesh Kumble Nayak (The Astrophysical Journal)
We investigate the measurement correlation between the effective spin and the effective tidal deformability in gravitational-wave signals from binary neutron star mergers. To efficiently measure the effective tidal deformability parameter, we exploit the fact that the tidal effects in a binary system are prominent when the components are closer, during the late inspiral. Thus, we indicate a computationally efficient strategy of extracting the tidal information compressed within the seconds before the merger. We report our observations for GW170817 and explore the suitability of our approach for the upcoming observation scenarios of the current and future ground-based observatories. Fast and accurate measurements of the tidal deformability parameters can be used to inform astronomers when prioritizing the electromagnetic follow-up efforts for such sources.